Providing Cancer Referral Service Applications for Village Communities - Yunike, Yunike; Kusumawaty, Ira; Sri Ananingsih, Esti; Podojoyo, Podojoyo; Elfrida, Solha; Monalisa, Monalisa; Inastyarikusuma, Tarrinni (Yayasan Rumah Ilmu Professor, 2024)
Cancer is one of the main causes of death in the world, including in Indonesia. Rural communities often face significant challenges in accessing adequate cancer health services, such as distance to health facilities, lack of transportation, and limited trained medical personnel. The research explores the need and potential benefits of providing a cancer referral service application in rural Indonesian communities. The research method used is qualitative with data collection through in-depth interviews and surveys of rural residents. The research results show that rural communities urgently need innovative solutions to overcome gaps in access to cancer health services. Respondents stated that traveling to health facilities in big cities requires significant costs and time so providing a cancer referral service application could be an effective solution. This designed application includes information about nearby health facilities, and mobile health service schedules and allows patients to make appointments and obtain referrals directly through their devices. This research found that the cancer referral service application can increase efficiency and effectiveness in providing cancer health services in rural areas. This application not only facilitates easier and faster access to health services but also raises public awareness regarding the importance of early detection and timely treatment. Active participation of local health workers and support from government and non-government organizations are critical to successfully implementing this application. It can be concluded that providing a cancer referral service application is an urgent need in rural communities in Indonesia. The app is expected to reduce disparities in access to cancer care and potentially save many lives through early detection and timely intervention. Health policies are needed to support the development and dissemination of this application, considering local wisdom and the specific conditions of each region.